3D bioprinting of biomimetic aortic vascular constructs with self‐supporting cells. Issue 4 (21st February 2015) - Kucukgul, Can; Ozler, S. Burce; Inci, Ilyas; Karakas, Ezgi; Irmak, Ster; Gozuacik, Devrim; Taralp, Alpay; Koc, Bahattin
ABSTRACT Cardiovascular diseases are the leading cause of deaths throughout the world. Vascular diseases are mostly treated with autografts and blood vessel transplantations. However, traditional grafting methods have several problems including lack of suitable harvest sites, additional surgical costs for harvesting procedure, pain, infection, lack of donors, and even no substitutes at all. Recently, tissue engineering and regenerative medicine approaches are used to regenerate damaged or diseased tissues. Most of the tissue engineering investigations have been based on the cell seeding into scaffolds by providing a suitable environment for cell attachment, proliferation, and differentiation. Because of the challenges such as difficulties in seeding cells spatially, rejection, and inflammation of biomaterials used, the recent tissue engineering studies focus on scaffold‐free techniques. In this paper, the development of novel computer aided algorithms and methods are developed for 3D bioprinting of scaffold‐free biomimetic macrovascular structures. Computer model mimicking a real human aorta is generated using imaging techniques and the proposed computational algorithms. An optimized three‐dimensional bioprinting path planning are developed with the proposed self‐supported model. Mouse embryonic fibroblast (MEF) cell aggregates and support structures (hydrogels) are 3D bioprinted layer‐by‐layer according to the proposed self‐supported method to form an aortic tissue construct. Biotechnol. Bioeng. 2015;112: 811–821. © 2014 Wiley Periodicals, Inc.